2020
DOI: 10.1007/s10900-020-00916-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Towards COVID-19 Among Ecuadorians During the Outbreak: An Online Cross-Sectional Survey

Abstract: Preventing the transmission of SARS-CoV-2 (causative agent for COVID-19) requires implementing contact and respiratory precautions. Modifying human behavior is challenging and requires understanding knowledge, attitudes, and practices (KAPs) regarding health threats. This study explored KAPs among people in Ecuador. A cross-sectional, internet-based questionnaire was used to assess knowledge about COVID-19, attitudes toward ability to control COVID-19, self-reported practices related to COVID-19, and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
98
6
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 31 publications
(33 reference statements)
25
98
6
9
Order By: Relevance
“…However, we cannot conclude that there is a growing participation of males in social science studies with the reason that the presence of male students at the time of the survey was more, as many studies on a similar topic have proved to have more female participation with a huge gap of leading as compared to the one found in our study. 15,[30][31][32][33] Furthermore, it is found that the majority of international students were young, single, and they were doing either medicine or engineering-related programs, something that mainly contributed to their protracted stay of more than 2 years, as many of these courses are up to 5 years before graduating. About studying in China, there are a lot of reasons behind the attraction of the two aforementioned courses, the main of which was that many Chinese universities are highly equipped with the state of the art technologies aptly positioned to provide the best training in the medical and engineering courses and also the affordability of academic expenses in China as compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot conclude that there is a growing participation of males in social science studies with the reason that the presence of male students at the time of the survey was more, as many studies on a similar topic have proved to have more female participation with a huge gap of leading as compared to the one found in our study. 15,[30][31][32][33] Furthermore, it is found that the majority of international students were young, single, and they were doing either medicine or engineering-related programs, something that mainly contributed to their protracted stay of more than 2 years, as many of these courses are up to 5 years before graduating. About studying in China, there are a lot of reasons behind the attraction of the two aforementioned courses, the main of which was that many Chinese universities are highly equipped with the state of the art technologies aptly positioned to provide the best training in the medical and engineering courses and also the affordability of academic expenses in China as compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 172 full-text articles were examined based on inclusion and exclusion criteria. Finally, thirteen (13) articles [30][31][32][33][34][35][36][37][38][39][40][41][42] were included in this systematic review. The PRISMA Statement flow diagram, that consisted of four phases i.e.…”
Section: Literature Searchmentioning
confidence: 99%
“…Factors such as gender, age, education level annual income and political preference have influenced the KAP about COVID-19 [30,31,35,36].…”
Section: General Publicmentioning
confidence: 99%
See 2 more Smart Citations